Hsp27 as a Therapeutic Target in Cancers - Acunzo, Julie; Andrieu, Claudia; Baylot, Virginie; So, Alan; Rocchi, Palma (Current Drug Targets, 2014)
Heat shock protein 27 (Hsp27), induced by heat shock, environmental and pathophysiological stressors, is a multidimensional protein that acts as a protein chaperone and an antioxidant. This protein plays a major role in the inhibition of apoptosis and actin cytoskeletal remodeling. This stress-activated protein is up-regulated in many cancers and is associated with poor prognosis as well as treatment resistance by protecting cells from therapeutic agent that normally induces apoptosis. This review highlights the most recent findings and role of Hsp27 in cancer and the different strategies to target and inhibit Hsp27 for clinical purposes.
Keywords: targeted therapy